DERMOID CYST IN SHEEP - A CASE REPORT - Pereira Stelmann, Ulisses Jorge (2012)
Stelmann U.J.P., Silva A.A, Souza B.G., Oliveira G.F., Mello E.B.F.R.B, Souza G.C.J. & Hess T.M. Dermoid cyst in sheep - A Case Report. [Cisto dermoide em ovino - Relato de Caso]. Revista Brasileira de Medicina Veterinaria, 34(2):127-130, 2012. Programa de Pos-Graduacao em Ciencia, Tecnologia e Inovacao em Agropecuaria, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Seropedica, RJ 23890-000, Brasil. E-mail: stelmann.ppgctia@gmail.comA dermoid cyst is a non-neoplasic, benign dermatologic injury. This article describes the finding of a dermoid cyst that was surgically extracted in a nine months aged ewe. The patient was admitted to the Large Animal Veterinary Hospital Department at the Federal Rural of Rio de Janeiro University, with a history of a non-healing wound that also contained fur. The ewe was referred to the surgical service and the histopathologic analysis of the lesion revealed a structure lined by stratified epithelium containing hair follicles, sudoriparous and sebaceous glands, which are conclusive for a dermoid cyst diagnosis.